2007
DOI: 10.1002/tox.20281
|View full text |Cite
|
Sign up to set email alerts
|

Serologic evaluation of human microcystin exposure

Abstract: Microcystins are among the most commonly detected toxins associated with cyanobacteria blooms worldwide. Two episodes of intravenous microcystin exposures occurred among kidney dialysis patients during 1996 and 2001. Analysis of serum samples collected during these episodes suggests that microcystins are detectable as free and bound forms in human serum. Our goal was to characterize the biochemical evidence for human exposure to microcystins, to identify uncertainties associated with interpretation of these ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 29 publications
1
26
2
Order By: Relevance
“…These results suggest that lower amounts of permanganate are insufficient to generate MMPB from cyanobacterial samples; therefore, oxidization of cyanobacterial samples with a high dose of permanganate in the reaction solution should be considered. These findings differ from those of previous studies, which have usually been conducted using lower concentrations of permanganate [38][39][40][41][42][43][44][45][46][47].…”
Section: Effect Of the Concentration Of Permanganate On The Yield Andcontrasting
confidence: 99%
See 2 more Smart Citations
“…These results suggest that lower amounts of permanganate are insufficient to generate MMPB from cyanobacterial samples; therefore, oxidization of cyanobacterial samples with a high dose of permanganate in the reaction solution should be considered. These findings differ from those of previous studies, which have usually been conducted using lower concentrations of permanganate [38][39][40][41][42][43][44][45][46][47].…”
Section: Effect Of the Concentration Of Permanganate On The Yield Andcontrasting
confidence: 99%
“…The results revealed that the yields of MMPB under neutral or alkaline conditions were higher than those under acidic conditions, with the highest concentration being produced under weak alkaline conditions (pH ∼9). These results are consistent with those of previous studies in which the pH of the solution was adjusted to approximately 9 using potassium bicarbonate to produce MMPB in oxidation reactions [38][39][40][41][42][43][44][45][46][47]. Among the five pH values evaluated, the resulting MMPB concentrations were shown to have only minor differences after 1 h, indicating that MMPB was stable under different pH conditions.…”
Section: Effect Of Ph On the Yield And Stability Of Mmpbsupporting
confidence: 90%
See 1 more Smart Citation
“…most widely used as extraction solvent in biological fluid samples [2,[28][29][30]. In the plasma preparation, methanol was chosen for further development as it had better recoveries (93.7%, 91.1% and 85.8% for MC-RR, MC-RR-GSH and MC-RR-Cys, respectively), which were obviously higher than those of acetonitrile (78.6%, 75.0% and 78.2%) and EDTA-Na 2 (0.01 M)-5% acetic acid (35.6%, 32.9% and 32.8%).…”
Section: Fig 3 Mean Recoveries Of Mc-rr Mc-rr-gsh and Mc-rr-cys Spmentioning
confidence: 99%
“…Microcystins (MCs) are a family of cyanotoxins along with the occurrence of toxic cyanobacterial blooms in eutrophic fresh and brackish waters [1,2]. To date, more than 80 structural analogs of MCs have been identified, and microcystin-RR (MC-RR) is one of the dominant variants in cyanobacterial blooms in lakes of China [3,4].…”
Section: Introductionmentioning
confidence: 99%